2022
DOI: 10.1021/acs.jafc.2c01035
|View full text |Cite
|
Sign up to set email alerts
|

High Value Utilization of an Avermectin Fermentation Byproduct: Novel B2a Derivatives as Pesticide Candidates

Abstract: In an effort to develop novel molecules with suitable insecticidal activities, 23,24-alkene-avermectin B2a derivatives have been synthesized via a one-pot multistep reaction using avermectin B2a, a byproduct of avermectin fermentation, as a starting material. All products and intermediates were characterized by 1 H NMR, 13 C NMR, and high-resolution mass spectrometry. Bioassay results showed that the LC 50 values of compounds 4 and 9 against Meloidogyne incognita were 0.63 and 0.50 mg/L, respectively, similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…79 Xu et al found that the insecticidal activities of a series of abamectin B2a derivatives against Tetranychus cinnabarinus, Mythimna separate, and Meloidogyne incognita were close to or even higher than those of abamectin, which is a potential insecticide friendly to the environment. 80 In addition, the insecticidal activities of compound 48 against Aedes aegypti and Musca domestica were demonstrably better than those of Pyrethrin and trans-chrysanthemic acid, 81 and the compounds high activity insecticidal results were confirmed via favorable combinations with the important active amino acids of Aedes aegypti target proteins. Tricyclic spiranoid lactones are also natural, bioactive chemicals, but fused lactones are rarely reported.…”
Section: ■ Insecticidal Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…79 Xu et al found that the insecticidal activities of a series of abamectin B2a derivatives against Tetranychus cinnabarinus, Mythimna separate, and Meloidogyne incognita were close to or even higher than those of abamectin, which is a potential insecticide friendly to the environment. 80 In addition, the insecticidal activities of compound 48 against Aedes aegypti and Musca domestica were demonstrably better than those of Pyrethrin and trans-chrysanthemic acid, 81 and the compounds high activity insecticidal results were confirmed via favorable combinations with the important active amino acids of Aedes aegypti target proteins. Tricyclic spiranoid lactones are also natural, bioactive chemicals, but fused lactones are rarely reported.…”
Section: ■ Insecticidal Activitymentioning
confidence: 96%
“…Compound 47 also reported its insecticidal activity against Bursaphelenchus xylophilus , and although the effects were lower than observed for avermectin, it provided ideas for the application of spironaphthalene derivatives in pesticides . Xu et al found that the insecticidal activities of a series of abamectin B2a derivatives against Tetranychus cinnabarinus , Mythimna separate , and Meloidogyne incognita were close to or even higher than those of abamectin, which is a potential insecticide friendly to the environment . In addition, the insecticidal activities of compound 48 against Aedes aegypti and Musca domestica were demonstrably better than those of Pyrethrin and trans -chrysanthemic acid, and the compounds high activity insecticidal results were confirmed via favorable combinations with the important active amino acids of Aedes aegypti target proteins.…”
Section: Insecticidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Avermectin is a sixteen-membered macrolide insecticide extracted from the MA-4680 strain of Streptomyces avermitilis that can be isolated from the soil. A number of avermectin derivatives exist, namely, A1a, A2a, A1b, A2b, B1a, B2a, B1b, and B2b, wherein avermectin B2 is known to exhibit a strong nematocidal activity. , Although this compound has been widely used to control crop diseases caused by infectious nematodes (e.g., root-knot nematodes, root rot nematodes, cyst nematodes, and stem nematodes), , it is susceptible to photolysis and a has poor mobility in the soil, thereby hindering its uptake by plants and lowering its potential efficacy . However, despite the fact that various avermectin B2 preparations are available on the market, such as emulsifiable concentrate (EC), microemulsion (ME), and emulsion in water (EW), , they are unable to solve the above issues.…”
Section: Introductionmentioning
confidence: 99%